РЕЗИСТЕНТНІ ДО 5-ФТОРУРАЦИЛУ КЛІТИНИ КОЛОРЕКТАЛЬНОГО РАКУ ХАРАКТЕРИЗУЮТЬСЯ ПІДВИЩЕНОЮ ІНВАЗИВНІСТЮ ТА ЕКСПРЕСІЄЮ βIII-ТУБУЛІНУ - Akalovich, S.; Portyanko, A.; Pundik, A.; Mezheyeuski, A.; Doroshenko, T. (PH Akademperiodyka, 2023)
Summary. Background: Elevated βIII-tubulin levels are associated with resistance to a broad spectrum of drugs in different carcinomas and with poor prognosis of various epithelial cancers. 5-Fluorouracil (5-FU) is a widely used standard drug in chemotherapeutic regimens for colorectal cancer treatment, although the resistance to 5-FU is a major obstacle to successful therapy. Aim: The aim of the study was to compare the invasive and adhesion properties and the expression levels of βIII-tubulin in a 5-fluorouracil (5-FU)-resistant colorectal cancer (CRC) cell line HCT116 and parental cells. Materials and Methods: The 5-FU-resistant cell line was established by continuous stepwise selection with increasing concentrations of 5-FU. Cell viability and properties were evaluated using MTT, adhesion and Transwell invasion assays, respectively. The expression of βIII-tubulin was revealed by immunoblot and immunofluorescence. Results: The derivative line is 25-fold more resistant to 5-FU and characterized by altered cell morphology. Twice as many cells of the 5-FU-resistant line fail to adhere as compared to the parental cell line. 5-FU-resistant cells are characterized by enhanced invasiveness, accompanied with the increased βIII-tubulin expression. In addition, we found that loss of βIII-tubulin expression was correlated with loss of 5-FU resistance. Conclusion: Our results indicate that even though 5-FU does not target microtubules, there appears to be a correlation between βIII-tubulin expression and resistance to 5-FU that is particularly important with regard to invasiveness. These findings indicate a possible contribution of βIII-tubulin to 5-FU resistance in vivo.